PENGARUH BEBERAPA JENIS MEDIUM TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN SETEK TANAMAN MAWAR (Rose sp) - Unip Serlina; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research is to get plant medium, dosage of NPK fertilizer and its interaction suitable for growth of cuttings of rose plants. This research has been conducted in Experimental Garden of Faculty of Agriculture, University of Riau. This research took place from October 2016 until January 2017. This research was conducted experimentally using Completely Randomized Design (RAL), Factorial and 3 replications. Factorial consists 2 factors. The first factor of planting medium (M) consists of 3 levels: M1 = Incepticol soil, M2 = sawdust, M3 = rice husk. The second factor of NPK (P) consists of 4 levels: P0 = without NPK, P1 = NPK 1 g/plant, P2 = NPK 2 g/plant, P3 = NPK 3 g/plant. Each unit consists of 2 plants of roses. Parameters those observed shoot lengths, number of shoots per plant, number of leaves per plant, age of first flower appeared, the number of flowers per plant and root length. The results obtained were analyzed using anova and HSD  of 5%. The results showed rice husk medium, the dose of NPK 1 g / plant fertilizer and better interaction in improving plant growth. Keywords:Setek roses, Medium plants, NPK Fertilizer.